A Pragma-Dialectical Approach to Trade Friction Discourse: A Case Study of a Public Letter in Sino-US Trade Friction on Tire Special Safeguard (Sinología hispánica. China Studies Review, 2016)
Based on the analytical framework ofStrategic Maneuvering, this paper analyzes andevaluates the public letter from China Chamberof Commerce of Metals, Minerals & ChemicalsImporters & Exporters (CCCMC) and China RubberIndustry Association (CRIA) to Obama andUnited States Trade Representative (USTR) onJuly 27th, 2009 to reveal the discursivestrategies and their corresponding linguisticrealizations manipulated in tire special safeguardcase. The research results show that, strategicmaneuvering in CCCMC & CRIA’s public lettersis integratedly realized through choice of topicalpotential, catering for audience demands andchoice of presentational devices, which issupported by such argumentative strategies aspresupposition, contrast, appeal to audience'svalues, appeal to authority, vagueness,repetition, statistics, appeal to opponent ’ sconcession, and the like. CCCMC & CRIA’s publicletter has its shortcomings in clarification ofdifference of opinion in the confrontation stage,in choice of starting in the opening stage, inchoice of topics in the argumentation stage andin manipulation of such specific argumentativerhetoricstrategies as ‘contrast’ and ‘statistics’.In view of China’s merits and deficiency, Chinashould: (1) clarify the confrontation, opening,argumentation and concluding stages of theargumentative discourse and flexibly set thedialectic and rhetoric aims of these four stagesaccording to the context; (2) strategicallymaneuver among topical potential, audiencedemand and presentational devices, in line withthe established dialectic and rhetoric aims indifferent argumentative stages; (3) recognizethe institutional context of trade frictiondiscourse and the importance of languageexpression, and cultivate an assertive image.